Improved Cardiorespiratory Fitness With Aerobic Exercise Training in Individuals With Traumatic Brain Injury. Issue 6 (November 2015) - Chin, Lisa M. K.; Chan, Leighton; Woolstenhulme, Joshua G.; Christensen, Eric J.; Shenouda, Christian N.; Keyser, Randall E.
Abstract : Objective: To examine cardiorespiratory fitness in individuals with traumatic brain injury (TBI), before and following participation in a supervised 12-week aerobic exercise training program. Methods: Ten subjects with nonpenetrating TBI (TBI severity: mild, 50%; moderate, 40%; severe, 10%; time since injury [mean ± SD]: 6.6 ± 6.8 years) performed exercise training on a treadmill 3 times a week for 30 minutes at vigorous intensity (70%-80% of heart rate reserve). All subjects completed a cardiopulmonary exercise test, with pulmonary gas exchange measured and a questionnaire related to fatigue (Fatigue Severity Scale) at baseline and following exercise training. Results: After training, increases ( P < .01) in peak oxygen consumption ( ; +3.1 ± 2.4 mL/min/kg), time to volitional fatigue (+1.4 ± 0.8 minutes), and peak work rate (+59 ± 43 W) were observed. At the anaerobic threshold, (+3.6 ± 2.1 mL/kg/min), treadmill time (+1.8 ± 1.1 minutes), and work rate (+37 ± 39 W) were higher ( P < .01) following exercise training. Subjects also reported significantly lower ( P < .05) Fatigue Severity Scale composite scores (−0.9 ± 1.3) following exercise training. Conclusion: These findings suggest that individuals with TBI may benefit from participation in vigorous aerobic exercise training with improved cardiorespiratory fitness and diminished fatigue.